An Evaluation of Human Resource Accounting on Corporate Performance - Lukman, Jimoh Adams; Abdulrasaq, Salman (Journal of Techno-Social, 2023)
The accounting component of human capital has not yet been fully adopted and implemented in corporate financial reporting of corporate organizations. Determining the impact of human resource accounting on turnover, earnings per share, and capital employed of corporate performance of the listed businesses in the Nigerian stock exchange is the goal of the current study. The results of the study demonstrate that (I) human resource accounting significantly influences business turnover, (ii) human resource accounting significantly influences earnings per share, and (iii) human resource accounting significantly influences return on capital employed. In conclusion, the financial reports would be more useful for making decisions if human resources were included as an asset rather than reported in the traditional manner. Therefore, the study suggests that the listed firms adopt a culture of valuing and disclosing education, training, and ongoing retraining of their human resources to enhance performance.